The Hypoxia-Mimetic Agent Cobalt Chloride Differently Affects Human Mesenchymal Stem Cells in Their Chondrogenic Potential - Gabriella Teti; Stefano Focaroli; Viviana Salvatore; Eleonora Mazzotti; Laura Ingra'; Antonio Mazzotti; Mirella Falconi (Hindawi Limited, 2018)
Adult stem cells are a promising cell source for cartilage regeneration. They resided in a special microenvironment known as the stem-cell niche, characterized by the presence of low oxygen concentration. Cobalt chloride (CoCl2) imitates hypoxia in vitro by stabilizing hypoxia-inducible factor-alpha (HIF-1α), which is the master regulator in the cellular adaptive response to hypoxia. In this study, the influence of CoCl2 on the chondrogenic potential of human MSCs, isolated from dental pulp, umbilical cord, and adipose tissue, was investigated. Cells were treated with concentrations of CoCl2 ranging from 50 to 400 μM. Cell viability, HIF-1α protein synthesis, and the expression of the chondrogenic markers were analyzed. The results showed that the CoCl2 supplementation had no effect on cell viability, while the upregulation of chondrogenic markers such as SOX9, COL2A1, VCAN, and ACAN was dependent on the cellular source. This study shows that hypoxia, induced by CoCl2 treatment, can differently influence the behavior of MSCs, isolated from different sources, in their chondrogenic potential. These findings should be taken into consideration in the treatment of cartilage repair and regeneration based on stem cell therapies.